Challenges Faced in Implementing Poverty Reduction Strategies and Development of Pro-Poor Urban Poverty Reduction Strategy Model in Eldoret Town, Kenya - Kipkemei, Felix B.; Cheserek, Grace (African Journal of Education,Science and Technology (AJEST), 2021)
Poverty is the state of being inferior in quality or insufficient in amount, on the basis of social, economic and political aspects. There are different ways to identify the types of Poverty which include Absolute, Relative, Situational, Generational, Rural and Urban Poverty. A study to assess urban poverty in Kenya estimated the percentage of urban poverty in Eldoret town at 35.5% with a population of 79.9% and 20.1% living in core urban and peri-urban respectively. World bank estimates that the pace of poverty reduction in Kenya is only at 1% per a year. At such a pace, poverty eradication can only be a dream. On Sustainable Development Goals of eliminating poverty, Kenya has a similar goal through vision 2030 to have poverty reduced to lower levels. The objectives of this study were to establish the challenges facing implementation of National Government Constituency Development Fund (NG- CDF), Older Persons Cash Transfer (OPCT) and National Hospital Insurance Fund (NHIF) and to develop a pro-poor urban poverty reduction strategy model. The major significance of this study was to highlight on pro-poor poverty reduction methodology by developing a pro-poor poverty reduction strategy model to inform policy. Literature review was done to establish facts as they are in other countries. The descriptive research design was adopted for this study to describe the situation on challenges faced in implementing poverty reduction strategies. Fischer’s formula was used to get a sample size of 273 respondents who formed government officials and household heads of low-income estates of Yamumbi and Msikiti localities in Langas estate, Mwitiriria and Bahati in Munyaka estate, and Kambi Teso and Bondeni in Kamukunji estate. This study targeted two major groups of persons: those in governance like in institutions e.g., hospitals, county government offices and schools formed key informants. The Key informants chosen gave specific information about the challenges faced in implementing NG- CDF, OPCT and NHIF as well as various ways to develop a pro-poor urban poverty reduction strategy model. The study used cluster sampling for 200 household heads in the three low-income estates, snowball sampling techniques to identify 58 respondents from beneficiaries of OPCT and purposive sampling technique to obtain data from 15 key informants. Questionnaires as well as interview schedules were employed to collect data. Pilot testing was carried out to check for reliability and validity of the tools. Descriptive statistics was used to analyze the data where chi square tests were carried out on the variable items to show the significance differences in the results. A proportion of (63.24%) of the respondents comprised of females. 83.27% of the respondents had formal education. Unemployed respondents constituted the highest percentage (86.40%). Those who owned the houses they lived in were (45.05%). The study revealed that the county government of Uasin Gishu had various strategies to reduce poverty such as NHIF (13%), Mama na kuku programme (18.2 %) kijana na acre programme (9.1%), Beyond Zero initiative (13%), water kiosks (4%) among others with a significance difference (χ2 = 21.23, d. f.=8, P = 0.0066). Respondents indicated that there were challenges that faced implementation of poverty reduction strategies in Eldoret town that included insufficient allocation of funds (45.0%) and misappropriation and corruption of public funds (25.0%). Some of identified urban poor coping strategies included use of microfinancing (76.5%) and use of seminars for education purposes with a significance difference (χ2 = 86.67, d.f=2, P< 0.0001). Respondents had the opinion that setting up dispensaries in every estate would be effective as poverty reduction strategy. The study came up with proposed pro-poor poverty Reduction strategy model with the following levels: The NHIF, OPCT, and the CDF levels. Challenges that would face the model would be decreasing profit margins for health insurance companies because they must now manage healthcare costs for people with pre-existing medical conditions and cover the entire costs of preventive services. In conclusion, the NHIF, the OPCT and the NG -CDF should be managed well by ensuring proper funding and enhanced transparency for reasons of accountability in order to bring significant change in the lifestyles of the urban poor measured by the changes in Social Economic Status’ indicators (SES) such as education, health facilities, security and empowerment. The study recommends that OPCT should be remitted every month consistently and money set aside should be enough to cater for poor person’s needs. The OPCT and NHIF of older people should be integrated to cater for monthly premiums due for NHIF cover. The CDF should focus on matters outside schools as well. The NHIF board should review its remittance policy so that unemployed and poor people should be given highly subsidized or even free treatment for whatever ailment they suffer from.